Mischief in the earth in the light of the Holy Qur’an: the case for preventing global warming as a fard Kifayah - Yaseen, Ghassan Taha (Universiti Sains Islam Malaysia (USIM), 2011)
Contemporary human civilization is facing a huge problem. One may refer to it as mischief in the Earth. Allah said: “Do no spread mischief on the earth, after it hath been set in order” (Surah Al-Ar’raf 7: 56), and also said “When he turns his back, his aim everywhere is to spread mischief through the earth and destroy crops and cattle. But Allah loveth not mischief” (Surah Al-Baqarah 2: 205)... In these verses and others are clear warnings from Allah to his slaves prohibiting them from committing evil on earth? The Holy Qur’an has identified all kinds, from private mischief to general mischief. This paper will focus on mischief in general, i.e. relating to the study of global warming, in spite of the difficulty to link with specific weather events to global warming. The increased in global temperatures may in turn cause broader changes, so this research will try to determine the reasons for these higher temperatures, which began two centuries ago and have increased since the middle of last century. The research will explain the causes and the results of global warming. Finally, the research will attempt to identify who is primarily responsible for the pollution of the environment, and what possible solution could be explored to get out of this dilemma. In addition, the legitimate ruling from the Islamic perspective will be considered in response to such a situation. I.e. is it fard Kifayah or Fardu ‘Ayn’?